To simplify `(k+3)-(3k-5)`

Multiply `-1` by each term inside the parentheses.

`k+3+5-3k `

Since `k` and `-3k` are like terms, add `-3k` to k to get `-2k` .

`-2k+3+5`

Add `5` to `3` to get `8` .

`-2k+8 `

Reorder the polynomial `-2k+8` alphabetically from left to right, starting with the highest order term.

`8-2k`

To simplify the expression `(k+3)-(3k-5)` , first we need to remove the parenthesis:

`= (k + 3) - (3k-5)`

`= k + 3 - 3k + 5`

Combine like terms.

`= 3 + 5 + k - 3k`

`= 8 - 2k`

Check if the resulting equation is factorable. In this case, it is factorable by 2. Factor out 2.

`= 2(4-k) ` **-> answer**

**QUESTION:-**

How do I simplify (k+3)-(3k-5)?

**SOLUTION:-**

(k+3) - (3k-5)

In order to solve this problem; we open up the brackets by multiplying each component of the second bracket with the minus sign:

= k + 3 -3k + 5

= k - 3k + 3 + 5

= -2k + 8

Or there is yet another way that this question can be further simplified;

= 2 (-k + 4) OR = -2 (k - 4)

Hence Solved

(k + 3) - (3k - 5)

To simplify this we can follow the rule of BODMAS or PEMDAS. First we have to remove the brackets,

k + 3 - 3k + 5

- 2k + 8

It cannot be simplified further so we factor out the above,

- 2k + 8

**- 2(k - 4) Answer**.

(k+3)-(3k-5)

distribute negative

k+3-3k+5

combine like terms

-2k+8 factor out

-2(k-4)

(k+3)-(3k-5)

the answer would be -2k+8 because all you do is subtract the ones with k and the regular numbers following your negative rules.

you can simplify this to 2(-k+4)

(k+3)-(3k-5)

k+3-3k+5 combine like terms

k-3k=-2k

3+5=8

-2k+8 is the answer or find the GCF

-2(k-4)